Geographical indication: Its contribution and legal protection in Malaysia and Indonesia - Mohd Noor, Nor Azlina; Abd Aziz, Ahmad Shamsul (Universitas Islam Riau Indonesia, 2010)
Geographical indication is one of the intellectual property law regimes. It is known as “the Sleeping Beauty” of the intellectual property world. It is so as although they have been around for a time in memorial, the widespread awakening as to their business value and economic contribution only occurred in recent years. Therefore, this paper seeks to establish the legal protection under geographical indication in Malaysia and Indonesia with special reference on its contribution to the economic growth.